High efficacy and retention rate of levilimab in the treatment of patients with rheumatoid arthritis in real-life practice - A. I. Zagrebneva; E. N. Simonova; Yu. A. Gavrikova; V. V. Dolgov; G. A. Togizbayev (Научно-практическая ревматология)
Previously published results of a retrospective analysis showed that switching to levilimab from other interleukin 6 receptor inhibitor (iIL6R) allows maintaining the achieved effect, and in some cases, increasing the effectiveness of treatment. This article presents the results of an extended observation period.The aim – to evaluate the efficacy, safety and retention rate of levilimab in patients with rheumatoid arthritis (RA) during one year of observation.Materials and methods. A retrospective analysis of data from the Moscow register of RA patients. The analyzed sample included RA patients who received levilimab 162 mg weekly after switching from other iIL6R (tocilizumab and sarilumab). Patient retention rate on levilimab therapy was assessed during 52 weeks of observation. The efficacy was evaluated at months 3, 6, 9 and 12 of levilimab therapy by the following parameters: laboratory markers of inflammation (C-reactive protein (CRP), erythrocyte sedimentation rate), assessment of the number of swollen (SJC) and painful (PJC) joints, assessment of the patient’s global assessment (PGA) by visual analogue scale (VAS), and DAS28-CRP (Disease Activity Score 28 with CPR).Results. 141 patients were included in analysis, the majority of patients were female (89%), the mean age was 57.8 years. The mean duration of levilimab therapy was 12.2±4.4 months. After 12 months of treatment, 87.5% [95% confidence interval: 82.1; 93.2] of patients continued levilimab therapy. Retention rate of levilimab therapy remained high in the levilimab monotherapy and combination therapy subgroups, and when prescribed as second or following biologic disease-modifying antirheumatic drugs (DMARDs). The mean DAS28-CRP, CRP level, TJC, SJC, and PGA by VAS were low at the time of initiation of levilimab therapy and remained stable during the year of therapy.Conclusions. Levilimab had high patient retention in therapy when used both as monotherapy and in combination with conventional synthetic DMARDs, as well as when prescribed in second and following lines of biologic DMARDs.